2008
DOI: 10.4049/jimmunol.180.1.444
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of LethalPlasmodium yoeliiMalaria following Protective Immunization Requires Antibody-, IL-4-, and IFN-γ-Dependent Responses Induced by Vaccination and/or Challenge Infection

Abstract: Immunization with Plasmodium yoelii merozoite surface protein (PyMSP)-8 protects mice from lethal malaria but does not prevent infection. Using this merozoite surface protein-based vaccine model, we investigated vaccine- and infection-induced immune responses that contribute to protection. Analysis of prechallenge sera from rPyMSP-8-immunized C57BL/6 and BALB/c mice revealed high and comparable levels of Ag-specific IgG, but differences in isotype profile and specificity for conformational epitopes were noted.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 67 publications
0
23
0
Order By: Relevance
“…Real-time PCR was used to quantitate the levels of PyMIF RNA using P. yoelii mif (pymif) forward primer 5Ј-TCAAAATGCGTTATCCGAAAT-3Ј and pymif reverse primer 5Ј-ACTTCCAGAAAATCGGAGGTT-3Ј as previously described (48). Assays were performed by using an Applied Biosystems 7900HT real-time PCR system (Applied Biosystems, Foster City, CA), and data were analyzed by using the Applied Biosystems sequence detection system (v2.2.1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Real-time PCR was used to quantitate the levels of PyMIF RNA using P. yoelii mif (pymif) forward primer 5Ј-TCAAAATGCGTTATCCGAAAT-3Ј and pymif reverse primer 5Ј-ACTTCCAGAAAATCGGAGGTT-3Ј as previously described (48). Assays were performed by using an Applied Biosystems 7900HT real-time PCR system (Applied Biosystems, Foster City, CA), and data were analyzed by using the Applied Biosystems sequence detection system (v2.2.1).…”
Section: Methodsmentioning
confidence: 99%
“…One week after this rechallenge, sera from the tertiary infection were collected for analysis of antibody responses. The level of anti-PyMIF antibodies present in serially diluted (1:100 to 1:3,200) sera from primary and tertiary P. yoelii 17X infection was measured by ELISA as previously described (48).…”
Section: S]methionine and [mentioning
confidence: 99%
“…Acquired immunity to blood-stage malaria infection is believed to depend on CD4 ϩ T cells (with their ability to secrete IFN-␥ making a contribution to their protective role) and antibody (36)(37)(38). As we were unable to purify memory CD4 ϩ T cells from WT and WSX-1 Ϫ/Ϫ mice for transfer into naive mice, we are unable to separate the contribution of the memory CD4 ϩ T cells to protection during secondary infection from any effect of humoral immunity.…”
Section: Cd44mentioning
confidence: 99%
“…Merozoite surface protein 8 (MSP8) is a target of protective, vaccine-induced antibody responses in the Plasmodium yoelii rodent model of malaria (11)(12)(13). Proof-of-concept studies showed that a high level of vaccine efficacy against challenge infection with lethal P. yoelii 17XL could be achieved by immunization of mice with a multicomponent vaccine including both P. yoelii MSP1 (PyMSP1) and PyMSP8 (14,15).…”
mentioning
confidence: 99%